Classroom settings for visually impaired schoolchildren: A scoping review. - Nur Aresya Ahmad Najmee; Zainora Mohammed; Mohd Harimi Abd Rahman; Norliza Mohamad Fadzil; Arimi Fitri Mat Ludin; Rosilah Hassan (PLoS ONE)
Visually impaired schoolchildren require classrooms tailored to their visual abilities and needs, as outlined in existing literature detailing optimal modifications, recommendations, and guidelines. The study aims to review existing literature on classroom modifications for visually impaired schoolchildren, outlining recommendations for creating ideal classrooms within mainstream physical settings. After initial screening, 712 publications (698 from databases and registers, and 14 from other methods) were identified for detailed review, of which 17 were ultimately eligible for inclusion. Through a systematic review of PubMed, Scopus, and Web of Science databases, along with additional sources up to February 2024, this research analyzed articles published from 1999 to 2024. A qualitative, thematic analysis was conducted on the included articles. Criteria included peer-reviewed journals, theses, and conference papers focusing on classroom settings for visually impaired schoolchildren aged 7 to 18. Key questions addressed are: 1) What classroom settings suit the needs of visually impaired schoolchildren? 2) What recommendations are tailored to visually impaired schoolchildren to create a conducive classroom environment? Analysis of 7 journal articles and 10 other publications revealed two main themes: optimizing classroom configuration and enhancing visual comfort. Articles primarily focused on suggestions for classroom layout, particularly furnishing arrangement (41%, n = 7) and enhancing lighting conditions (41% n = 7). However, concerns were raised about standard furniture designs and the need for tailored seating arrangements to meet the visual demands of visually impaired schoolchildren. Conclusion: This review provides valuable insights into creating optimal classroom settings for visually impaired schoolchildren, ensuring equal learning opportunities in a supportive environment tailored to their needs.